Smectic phase in suspensions of gapped DNA duplexes - Miroslaw Salamonczyk (Nature Portfolio, 2016)
DNA can be used as a tunable building block to create a variety of self-assembly-driven liquid crystals. Here, the authors report the stabilization of a smectic-A liquid crystal phase, where constituent molecules—two rigid dsDNA segments linked by a flexible ssDNA spacer—attain a folded configuration.